PAPER-ZNO NANO COMPOSITE PAPER FOR ANTIMICROBA PACKAGING APPLICATIONS - Cut Nurul Fitriyani; Teuku Rihayat; Aida Safitri; Shafira Riskina; Nurhanifa Nurhanifa (Politeknik Negeri Lhokseumawe, 2019)
Development and innovation for both antimicrobial functional packaging (active packaging and nanocomposite materials) from renewable polymers. This study aims to include ZnO nanoparticles in PLA (Polylactic Acid) paper layers in antimicrobial packaging applications. The method used for the manufacture of ZnO nanoparticles is the precipitation method and heating method in the manufacture of PLA-ZnO nanocomposite by varying 0.5%, 2% and 3.5% ZnO NP. The results obtained are in SEM images showing that the nanoparticles are distributed homogeneously on the surface. Antimicrobial tests showed that nanocomposite worked effectively in deactivating E. coli and S. aureus. Furthermore, E. coli was found to be more susceptible to this type of nanocomposite, showing a reduction of 3.4 log to 3.5% ZnO loading in the PLA layer. Based on the results, it can be explained that the ZnO nanoparticles have several active mechanisms, and different antimicrobial testing methods can only activate some of the mechanisms. In addition, nano-activated packaging materials for food contact applications and market prospects are analyzed.